2011
DOI: 10.1108/01443331111177869
|View full text |Cite
|
Sign up to set email alerts
|

Smuggling and small‐scale trade as part of informal economic practices

Abstract: Purpose -Using small-scale cross-border trade and smuggling as an example of an informal practice carried out in many post-socialist countries, the purpose of this paper is to explore which different meanings this activity possesses for the people being involved in it and in how far small-scale cross-border trade is being accepted and looked at by society. The authors hope to show the different connections between informal and formal activities and specificities of localities which people in the mentioned coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Also, the boundaries between what considers illicit activities and informal activities, frequently used to theorize informal entrepreneurship (Godfrey 2011;Webb et al 2009), are fuzzy and permeable as has been shown for the case of crossborder entrepreneurship and petty trading (Bruns et al 2011;Karjanen 2011;Welter and Xheneti 2013).…”
Section: Different Shades Of Grey Black and White Entrepreneurshipmentioning
confidence: 97%
“…Also, the boundaries between what considers illicit activities and informal activities, frequently used to theorize informal entrepreneurship (Godfrey 2011;Webb et al 2009), are fuzzy and permeable as has been shown for the case of crossborder entrepreneurship and petty trading (Bruns et al 2011;Karjanen 2011;Welter and Xheneti 2013).…”
Section: Different Shades Of Grey Black and White Entrepreneurshipmentioning
confidence: 97%
“…It would also enable a "high road" rather than "low road" approach by shifting toward greater regulatory standards on working conditions such as health and safety and labour standards (Grabiner, 2000;Renooy et al, 2004;Williams and Windebank, 1998). Meanwhile, for informal enterprises, the key benefits are that they escape the pressure to enter exploitative relationships with the formal economy (Gallin, 2001;Williams and Windebank, 1998) and achieve the same levels of legal protection as formal enterprises (Boels, 2014;Bruns et al, 2011;ILO, 2014;Morris and Polese, 2014). They are also able to secure formal intellectual property rights for their products and processes (De Beer et al, 2013) and overcome the structural impediments that prevent them growing, such as their lack of access to advice and support as well as capital (ILO, 2014).…”
Section: Formalize Informal Enterprisementioning
confidence: 99%
“…The main reasons are interested in business, gain better income and prefer to be self-employed. The same situation occurs in the research carried out among informal cross-border traders between South Africa and the neighboring countries (Peberdy, 2000) and Eastern external European Union borders (Bruns, Miggelbrink & Muller, 2011) whereby respondents are also primarily driven by the income-earning opportunities available. The involvement of informal cross-border trade between Mozambique and its neighbours is also to gain extra income whilst informal cross-border traders in Zimbabwe are mainly driven by friendship (Muzvidziwa, 2001).…”
Section: Determinants Of Trade Participationmentioning
confidence: 89%